Self-citation Status Of Iranian Prolific Authors In The Field Of Medicine And Its Impact On The Hirsch Index In Web Of Science Database - SJ Ghazimirsaied; M Hemmat; H Dargahi; J Khansari (Tehran University of Medical Sciences, 2011)
Background and Aim: Using Hirsch index as an important tool to describe the scientific outputs of researchers has caused some authors to increase their self-imposed parameters, increase, citing themselves. Therefore it is necessary to consider the effect of self-citation on Hirsch index for every author to have better measuring on the quality of researchers scientific production.Materials and Methods: This research is descriptive method of citation analysis in general and specifically self-citation analysis. The study, are Iranian prolific authors in the field of medicine that have at least 30 documents indexed in Web of Science database between 2004 to 2006. Citations following up was studied till December 2010 Results was analysis using Excel software version 2007.Results: The average self-citation observed between prolific authors in medical field was 25/89 percent. Hirsch index for 30/77 percent of authors had changed considerably. The authors rating scheme based on Hirsch index was done after removing self - citation so that 38/46 percent of authors decreased to lower level.Conclusion: Considering that 10 to 30 percent of self-citation can be normal and justified, the status of self-citatin of Iranian prolific authors in medical field is desirable. Also, lower rates of self - citation of these authors doesnot affect Hirsch index.